MiR-429 increases the metastatic capability of HCC via regulating classic Wnt pathway rather than epithelial–mesenchymal transition. Issue 1 (1st August 2015) - Tang, Jing; Li, Liang; Huang, Wentao; Sui, Chengjun; Yang, Yingcheng; Lin, Ximeng; Hou, Guojun; Chen, Xin; Fu, Jing; Yuan, Shengxian; Li, Shao; Wen, Wen; et al.
Highlights: We demonstrated a novel functional axis involving miR-429/PTEN/PI3K/AKT for the manipulation of tumor metastasis. Five hypomethylated sites upstream of miR-429 cluster was identified in portal vein tumor thrombus tissues. miR-429-induced nucleus relocation of β-catenin was identified as the adverse prognosis factors for HCC survival. Abstract: Epigenetic modification of miR-429 can manipulate liver T-ICs via targeting the RBBP4/E2F1/Oct4 axis, which might be crucial for hepatocarcinogenesis. However, whether miR-429 plays a role in regulating metastasis of hepatocellular carcinoma is still unclear. Using quantitative methylation analysis and real-time PCR, we have identified the hypomethylated status and upregulation of miR-429 in portal vein metastasis samples in comparison with their matched primary tumor. The ectopic expression of miR-429 dramatically induced the expression of MMP2/7/9 and enhanced HCC migration and invasion in vitro and in vivo in an EMT-independent manner. Both bioinformatics and functional studies elucidated the direct regulation of miR-429 on the 3′UTR of the PTEN gene, which leads to the activation of PI3K/AKT signaling and the nuclear translocation of β-catenin, eventually. Conversely, the knockdown of miR-429 efficiently recovered the expression of PTEN and attenuated PI3K/AKT/β-catenin-mediated cell metastasis. Clinically, the higher expression of miR-429 and nucleus relocation of β-catenin were identified as the adverse prognosis factors for recurrence-free survival (RFS) and overall survival (OS). In summary, our results here defined miR-429 as a key inducer for HCC pathogenesis and metastasis with potential utility for tumor intervention.